Basic pattern design for care dependent elderly - Caldas, Artemisia (2017)
This study presents the first results of a PhD in textile engineering aiming to understand the clothes needs of the female elderly who are under the care of professionals or relatives. The initial body measurements of the elderly with and over 65 and the way they will impact in the basic pattern design are presented. A new concept of clothing is proposed, based in the shape and proportions of their bodies, considering their anatomic positions and their needs and limitations during the task of dressing/undressing and seeking the comfort of the user with the handling of the caregiver. The most common profile of these women corresponds to individuals that spend a great part of their day in a sitting position, in wheelchairs or in a conventional seat. After an ergonomic analysis, with the use of specific measurements, it was possible to perform a basic pattern design for this target population, which will after be used in the production of the appropriate clothing prototypes, respecting their needs. 78 measurements of elderly women in a sitting position were obtained, 46 in two institutions in the city of Guimaraes (Portugal) and 32 in two institutions in the city of Teresina (Brazil). 8 body measurements were considered to build an average measurements table from pre-established criteria for the construction of the clothing prototypes.